Analysis of attitudinal resources in China-related news in The Star Online - Hong, Wu; Kesumawati A. Bakar,; Azhar Jaludin,; Norsimah Mat Awal, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The portrayal of nations in media discourse not only reflects current events but also potentially shapes public perceptions and relationships between countries. This study examines the representation of China, Malaysia's largest trading partner, in Malaysian news, an area previously under-explored. Utilising the Appraisal Framework, we examine attitudinal resources that describe China, thereby assessing how the nation is linguistically and semantically positioned in The Star Online, a leading Malaysian news source. To reveal the underlying attitudes towards China, this study adapts the existing scheme of the UAM CorpusTool for detailed annotation, examining one representative news article from each year over a decade (2012-2021) in The Star Online. Our findings reveal: 1) positive attitudes prevail in the selected news articles; 2) linguistic resources of Judgment are predominant among the three attitudinal types, which means evaluation of behaviours is observed more often in the selected news; 3) the positive attitudes towards China reflect Malaysians' positive perception of China's economic strength, reliability, and optimistic outlook on favourable outcomes in the future. The results reflect a generally positive attitude towards China in The Star Online, which not only verify the workability of the theory, method, and instrument used in discourse analysis but also enrich the study of Malaysian news discourse.